Whole secretome of mesenchymal stem cells is fully incorporated in lipid bicontinuous cubic phases - Barata-Antunes, Sandra; Sousa, Rui A.; Salgado, António J.; Silva, Bruno F. B. (Frontiers in Medical Engineering, 2025)
Lipid bicontinuous cubic phases are precursors to cubosomes–a promising type of nanoparticle for the delivery of multicomponent biomolecular mixtures for applications in health such as regenerative medicine and wound healing. In this study, we showed that the secretome of mesenchymal stem cells (MSCs), a complex mixture of growth factors, cytokines, extracellular vesicles, and other cell-secreted molecules with therapeutic potential, can be fully incorporated into the bicontinuous cubic phases of phytantriol and monoolein. When the secretome was added to dry lipid films, the resulting partial phase diagrams of these lipid-secretome systems, although more complex, resemble those of their lipid-water analogs. Remarkably, visual inspections and Small-Angle X-ray Scattering (SAXS) studies showed composition regions of homogeneous solid-like lipid mesophases without excess liquid phase-separation. This indicates that the diverse secretome components, even with their varied sizes and structures, are fully integrated into the cubic phases. SAXS showed patterns dominated by bicontinuous cubic phases with structural parameters close to the lipid-water systems. This suggests that water-soluble proteins likely localize within the water channels of the bicontinuous cubic phase, which must exhibit flexibility to accommodate proteins of diverse sizes, likely through the formation of locally disordered channels. Extracellular vesicles and associated membrane proteins, on the other hand, are likely fusing with and integrating into the cubic membranes. These findings underscore the potential of such liquid crystalline materials as matrices for the entire secretome, paving the way for future secretome-based cell-free therapeutics such as tissue regeneration, neuroprotective and anti-inflammatory treatments.